37th British Mass Spectrometry Society annual meeting. (March 2017) - Wright, Patricia; Eckers, Christine
The 37th British Mass Spectrometry Society (BMSS) annual meeting took place over a brilliantly sunny 3 days by the sea in the historic Eastbourne Winter Gardens on the south coast of England. It was held between 13 and 15 September 2016. Two-hundred attendees enjoyed a conference covering all aspects of MS with speakers drawn from across Europe and North America. The BMSS is particularly proud of the encouragement it offers students and early career scientists, both financially in the form of travel grants and also in terms of opportunities to present at an international level in a supportive atmosphere. Further encouragement to newcomers to the field is offered in the form of the Barber Prize for best oral presentation and the Bordoli Prize for the best poster. This year's winners were Patrick Knight (University of Leeds), the Bordoli Prize for the poster 'Characterising the Interaction of Ataxin-3 and the Poly-Glutamine Aggregation Inhibitor QBP1'; Lisa Deininger (Sheffield Hallam University), the Barber Prize for 'Out Damned Spot! Bottom Up Proteomics for the Analysis of Bloodied Fingermarks'. In addition, the Delegates Choice for best poster went to Hannah Britt (Durham University) for 'Monitoring Reactions of Small Molecules with Cell Membranes by Liquid Chromatography–Mass Spectrometry'. For services to the MS community, Professor Gareth Brenton (Swansea University) was awarded the BMSS Medal; Professor Alison Ashcroft (Leeds University) and Anna Upton (former BMSS administrator) were given lifetime membership of the BMSS.